2018
DOI: 10.1016/j.aim.2017.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Auslander–Gorenstein algebras and precluster tilting

Abstract: Abstract. We generalize the notions of n-cluster tilting subcategories and τ -selfinjective algebras into n-precluster tilting subcategories and τn-selfinjective algebras, where we show that a subcategory naturally associated to n-precluster tilting subcategories has a higher Auslander-Reiten theory. Furthermore, we give a bijection between n-precluster tilting subcategories and n-minimal Auslander-Gorenstein algebras, which is a higher dimensional analog of AuslanderSolberg correspondence (Auslander-Solberg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 37 publications
1
51
0
Order By: Relevance
“…Recently Iyama and Solberg defined m-Auslander-Gorenstein algebra in [18]. They also showed that the notion of m-Auslander-Gorenstein algebra is left and right symmetric.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Iyama and Solberg defined m-Auslander-Gorenstein algebra in [18]. They also showed that the notion of m-Auslander-Gorenstein algebra is left and right symmetric.…”
Section: 3mentioning
confidence: 99%
“…[18] An artin algebra Λ is called m-Auslander-Gorenstein 1 if injdim Λ Λ ≤ m + 1 ≤ domdim Λ.Proposition 2.4.9. [18, Proposition 4.1] Let Λ be an artin algebra.…”
mentioning
confidence: 99%
“…Recently, Iyama and Solberg defined m-Auslander-Gorenstein algebras in [7]. They also showed that the notion of m-Auslander-Gorenstein algebra is left and right symmetric.…”
Section: Properties Of the Subcategory C λmentioning
confidence: 99%
“…Auslander-Solberg and Auslander correspondence. The Auslander-Solberg correspondence, which is defined by Iyama and Solberg [IS18], characterizes algebras Λ with domdim Λ ≥ k + 1 ≥ id Λ. In the case k = 1, this result is due to Auslander-Solberg [AS93a].…”
Section: Classical Casementioning
confidence: 99%